The role of international financial organizations in supporting Ukraine’s agricultural sector during the war - Lytvyn, Inna (My University, 2025)
The article examines the role of international financial organizations in supporting Ukraine’s agricultural sector during the war. It analyzes the assistance mechanisms implemented by the World Bank, the European Bank for Reconstruction and Development (EBRD), and the Food and Agriculture Organization of the United Nations (FAO), including credit programs, grants, humanitarian aid, and technical support. The study highlights the key results of these initiatives in 2022–2024, such as the stabilization of agricultural production, ensuring enterprise liquidity, supporting small and medium-sized farmers, and strengthening national food security. The paper emphasizes the importance of combining financial, trade, and humanitarian instruments to enhance the resilience of Ukraine’s agricultural sector and outlines the main challenges and priorities for further cooperation with international financial institutions. У статті розглядається роль міжнародних фінансових організацій у підтримці сільськогосподарського сектору України під час війни. Аналізуються механізми допомоги, що впроваджуються Світовим банком, Європейським банком реконструкції та розвитку (ЄБРР) та Продовольчою та сільськогосподарською організацією Об'єднаних Націй (ФАО), включаючи кредитні програми, гранти, гуманітарну допомогу та технічну підтримку. У дослідженні висвітлено ключові результати цих ініціатив у 2022–2024 роках, такі як стабілізація сільськогосподарського виробництва, забезпечення ліквідності підприємств, підтримка малих та середніх фермерських господарств та зміцнення національної продовольчої безпеки. У статті наголошується на важливості поєднання фінансових, торговельних та гуманітарних інструментів для підвищення стійкості сільськогосподарського сектору України та окреслюються основні виклики та пріоритети подальшої співпраці з міжнародними фінансовими установами.
Keywords: кафедра міжнародної економіки; international financial organizations; Ukraine’s agricultural sector; war; World Bank; financial support; food security; recovery programs; humanitarian assistance; гуманітарна допомога; міжнародні фінансові організації; сільськогосподарський сектор України; війна; Світовий банк; фінансова підтримка; продовольча безпека; програми відновлення